Mitochondrial DNA barcodes provide insight into the phylogeography and subspecies controversy in the widespread Neotropical white peacock butterfly, Anartia jatrophae (Nymphalidae: Nymphalinae). (14th July 2020) - Pfeiler, Edward; Nazario-Yepiz, Nestor O; Hernández-Cervantes, Pablo Luis; Markow, Therese Ann
Abstract: The validity of subspecies designations in the common and wide-ranging Neotropical white peacock butterfly, Anartia jatrophae, has been debated for decades and remains an unsettled and contentious taxonomic issue among lepidopterists. Originally described by Linnaeus in the mid-18 th century from specimens obtained from northern South America (Suriname), subsequent authors proposed a variety of subspecies names based on differences in adult external morphology among geographical populations. Many of these differences, however, were subsequently found to occur seasonally within populations, leading some to conclude that only a single polymorphic species should be recognized. Here, we have analysed both new and publicly available mitochondrial DNA barcodes, obtained from specimens collected from southern USA to northern Argentina, to assess whether they could provide insight into this long-standing controversy. Our molecular analyses, using a combination of character-based (nucleotide composition), population genetic and phylogenetic approaches, indicated the presence of at least four distinct genetic lineages that we suggest are distinct at the subspecies level, namely A. j. jatrophae, A. j. luteipicta, A. j. saturata and A. j. semifusca . Justification for these assignments and the proposed geographical distribution of each subspecies within the Americas are discussed.